XRCC1 R194W and R399Q Polymorphisms and Colorectal Cancer Risk in a Northeastern Mexican Population - Juan Pablo Meza-Espinoza; Valeria Peralta-Leal; Jorge Durán-González; Nelly Macías-Gómez; Anabel Bocanegra-Alonso; Evelia Leal-Ugarte (Genetics Research)
Colorectal cancer (CRC) is one of the most common cancers worldwide. Its etiopathogenesis is complex, mainly influenced by genetic instability caused by the accumulation of mutations. The XRCC1 gene, which is involved in DNA repair, has been associated with CRC through the R194W (C194T) and R399Q (G399A) polymorphisms, but the results are inconsistent. Here, we analyzed the association of these polymorphisms with sporadic CRC in a northeastern Mexican population, including 155 male CRC patients and 155 male controls. Genotyping was performed using the RFLP method. An association with CRC was found for the 399A allele (G vs A; OR = 1.48 (1.03–2.13), P=0.034) and for the 399AA genotype in a codominant model (AA vs GG; OR = 3.11 (1.06–9.10), P=0.031). In contrast, there were no significant differences between CRC patients and controls for the C194T polymorphism (C vs T; OR = 0.82 (0.52–1.31), P=0.41). These results are consistent with many similar studies, but further research is needed to verify whether the XRCC1 R194W and R399Q polymorphisms play a role in CRC etiology. The functional significance of these polymorphisms is unclear, but some studies suggest that they influence DNA repair capacity and, thus, cancer risk.